PENGELOLAAN HUTAN LINDUNG BUKIT BETABUH BERKELANJUTAN DI KABUPATEN KUANTAN SINGINGI, RIAU - Lilis Kurnia; Ridwan Manda Putra; Suwondo Suwondo (Program Pascasarjana Universitas Riau, 2020)
The study of the sustainability level of Bukit Betabuh Protection Forest, is intended to determine the status of sustainabilty, and lever attributes in the management of Bukit Betabuh protection Forest. This study was conducted with a multi-dimensional scaling analysis (MDS) approach with the help of Rapfish software. The research was conducted from August-september 2019 in the Bukit Betabuh Protection Forest area. Research objectives are analyzing the existing condition of Bukit Betabuh Protection Forest, Analying the sustainability status of Bukit Betabuh Protection Forest, Analyze levers that take effect Bukit Betabuh Protection Forest, and Designing the formulation of Bukit Betabuh Protection Forest.The research methods include : 1) Data collection methods (surveys, field measurements, sampling, intervies, and library research), 2) Data analysis methods (descriptive analysis of the ecological characteristics of protected forest, economic and social communities around the Bukit Betabuh Protection Forest, MDS analysis with Rapforest techniques to determine the level of sustainabillity in the management of the Bukit Batabuh Protection Forest). Based on the research that has been done, it turns out that the management of Bukit Batabuh Protection Forest shows that there is an imbalance in the dimensions (ecological, economic and social). The sustainability status of Bukit Batabuh Protection Forest is currently multidimensional, including the catagory of moderately sustainable with a sustainability index value of 55 %. Meanwhile, the result of the analysis of each dimension showed that the ecological dimension of the sustainability index was 63,4 % and the social dimension was 61,25 % which meant that it was quite coninous. Whle yhe economic dimension of sustainability index is 43,0 % which means it is not sustainable.